Ectopic Functioning Adrenocortical Oncocytic Adenoma (Oncocytoma) with Myelolipoma Causing Virilization - Lea F. Surrey; Ashesh A. Thaker; Paul J. Zhang; Giorgos Karakousis; Michael D. Feldman (Case Reports in Pathology)
Functioning adrenal adenomas are well-described entities that can rarely occur outside the adrenal gland in the ectopic adrenal tissue. Similarly, myelolipoma is an another benign lesion of the adrenal tissue which can rarely occur outside the adrenal gland. We report the first case of a testosterone producing an extra-adrenal adrenocortical oncocytoma accompanied by a myelolipoma. The patient presented with virilization and elevated androgen levels. Imaging revealed a retroperitoneal mass, which histologically consisted of oncocytes and intermingled myelolipoma. Postoperative androgen levels decreased to normal. The tumor cells were strongly positive for inhibin and Melan-A, supporting the adrenal origin. This case demonstrates a diagnostic challenge in which correlation with histology, immunohistochemistry, and serum endocrine studies led to the final diagnosis.